Utilization of Sulfur and Zinc Fertilizers Combined with Local Compost in Farmer-Livestock Groups of Satwa Winangun, Tangkas Village, Klungkung Regency, Bali - Mahardika, Ida Bagus Komang; Situmeang, Yohanes Parlindungan; Prakerti, Ni Luh Adelia Darma; Pratiwi, Ni Putu Yuliari Nanda (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Farmer-Livestock Group Satwa Winangun in Tangkas Village, Klungkung Regency, faces challenges in improving agricultural productivity and soil health due to excessive use of chemical fertilizers. This Community Service Program (CSP) aimed to introduce and implement the utilization of sulfur and zinc fertilizers combined with locally produced compost as environmentally friendly and sustainable alternatives. The program was conducted through training sessions, field demonstrations, and intensive mentoring for farmers. The results indicated significant improvements in soil fertility, plant growth, and production cost efficiency. Sulfur and zinc fertilizers enhanced soil structure and nutrient absorption, while local compost derived from village organic waste contributed to waste reduction and improved soil quality. Farmers began to adopt these methods independently and demonstrated strong enthusiasm toward sustainable agriculture practices. Overall, this program successfully empowered the farmer group through appropriate technology and the use of local resources. Beyond increasing agricultural yields, the activities also strengthened environmental awareness and encouraged farmer self-reliance in managing land productively and sustainably.